Pertumbuhan Beberapa Jenis Pohon Leguminosa Pada Media Tanam Tanah Bekas Tambang Emas Di Poboya Sulawesi Tengah - Abd Rauf; Wardah Wardah; Zulkaidah Zulkaidah (Mitra Sains, 2020)
This research aims to find out the growth of leguminosae tress on the different ex- Poboya soil mediums. It was conducted for three months since March until July 2019 taken a place at the Permanent Seedbed of BP-DAS Palu-Poso, Tadulako University by means of completely randomized design with plot split model which the leguminosae trees as main plot consist of Leucaena leucocephala, Sesbania grandiflora, Indigofera zollingeriana, Adenanthera pavonina and soil mediums as sub-plot include not contaminated, tailing, and contaminated soils as well as those medium types each mixed with compost. The results show that the interaction of leguminosa species and soil mediums presents obvious effect toward the diameter growth. Leucaena leucocephala and uncontaminated soil mixed with compost has better growth for 4,2 mm. The type of (Leucaena leucocephala) gives the best result while not contaminated soil mixed with compost conributes the best influence for all growth parameters of sampled leguminosa trees.